AKT Inhibitor Capivasertib as a Target for Osimertinib Combination Therapy in Lung Adenocarcinoma with EGFR Mutation - Takuya Tokunaga; Yuka Ishihara; Aya Harada Takeda; Yuya Tomioka; Ayako Nagata; Mayuko Kato; Takayuki Suetsugu; Keiko Mizuno; Kazuhiro Ueda; Naohiko Seki (Genes, 2026)
Background/Objective: An analysis of microRNA (miRNA) expression signatures in lung adenocarcinoma (LUAD) harboring EGFR mutations revealed that multiple miRNAs, including miR-126-3p, were suppressed in cancer tissues. This study focused on miR-126-3p and aimed to identify therapeutic target genes regulated by miR-126-3p in LUAD harboring EGFR mutations and evaluate their potential for combination therapy with EGFR tyrosine kinase inhibitors. Methods: The antitumor function of miR-126-3p was analyzed by the ectopic expression of miR-126-3p into LUAD cells with EGFR mutation. The target genes of miR-126-3p were identified through an analysis of the TargetScan, Genecodis 4 and TCGA databases. The Chou–Talalay method was used to determine the potential synergistic effects of selected drug combinations. Results: The expression of miR-126-3p attenuated the malignant transformation of LUAD cells through targeting the “EGFR tyrosine kinase inhibitor resistance pathway”. We focused on AKT2 among the genes involved in this pathway. Capivasertib was recently approved as the first inhibitor of oncogenic AKT signaling. Therefore, we investigated the effect of combination therapy comprising osimertinib and capivasertib on LUAD cell viability. Combination therapy synergistically reduced cell viability in both PC9 and H1975 cells, with combination index values of 0.61 and 0.14, respectively, at Fa = 0.5. Conclusions: Our miRNA-based analysis is an excellent strategy for identifying therapeutic targets that enhance the effects of EGFR inhibitors on LUAD.